Analisis Pengaruh Gaya Kepemimpinan Terhadap Kinerja Karyawan Di Lingkungan Perusahaan Modern - Shabrina (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the influence of leadership styles on employee performance in modern corporate environments. The research employed a quantitative explanatory approach with a sample of 100 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed through multiple linear regression with the aid of SPSS version 26. The results indicate that both transformational and transactional leadership styles have a positive and significant impact on employee performance, with transformational leadership showing a stronger influence. The coefficient of determination (R²) of 0.68 demonstrates that 68% of the variation in employee performance can be explained by these two leadership styles. The findings reinforce Bass and Riggio’s (2006) theory, which highlights that transformational leadership enhances motivation, commitment, and performance through inspiration and individualized consideration. This research provides theoretical contributions to the development of human resource management studies and practical implications for organizations to adopt effective and adaptive leadership styles in modern work environments.